The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1142/s0218301317500719
|View full text |Cite
|
Sign up to set email alerts
|

Transverse momentum fluctuation under the Tsallis distribution at high energies

Abstract: We studied the effects of the Tsallis distribution on the transverse momentum fluctuation in high energy collisions. The parton-hadron duality and the Bose-Einstein type correlation between partons were assumed. The fluctuation was calculated in the boost-invariant picture for the expectation value used in the Boltzmann-Gibbs statistics and for the expectation value used in the Tsallis nonextensive statistics. It was shown that the fluctuation is a function of η which is the ratio of the inverse temperature to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The results obtained here have shown that a system with fractal structure, similar to the thermofractals [25], can be understood as a natural consequence of the scale invariance of gauge field theories. We give solid grounds for phenomenological approaches that have been used to describe hadron mass spectrum [30] and multiparticle production with non extensive statistics [28][29][30][31][32][33][34][35][36][37][38], which can explain the long tail distribution observed in multiparticle production. From the recurrence method used here we understand the reason why, even at small order of perturbative QCD calculation, it is possible to describe correctly the transversal momentum distributions measured at high energies by adopting Tsallis distribution [39].…”
Section: Mainmentioning
confidence: 99%
“…The results obtained here have shown that a system with fractal structure, similar to the thermofractals [25], can be understood as a natural consequence of the scale invariance of gauge field theories. We give solid grounds for phenomenological approaches that have been used to describe hadron mass spectrum [30] and multiparticle production with non extensive statistics [28][29][30][31][32][33][34][35][36][37][38], which can explain the long tail distribution observed in multiparticle production. From the recurrence method used here we understand the reason why, even at small order of perturbative QCD calculation, it is possible to describe correctly the transversal momentum distributions measured at high energies by adopting Tsallis distribution [39].…”
Section: Mainmentioning
confidence: 99%
“…Since then, the Tsallis-like single particle distributions have been used in many branches of natural [8][9][10][11][12][13][14][15][16][17] and social sciences [18][19][20], and the field of high energy collisions is no exception [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. These studies have now established that the a global observable like the hadronic transverse momentum distribution generated from the high energy collisions (of protons on protons, for example) is describable by the 'Tsallis-like' distributions up to a very high range of transverse momentum (p t ) [37].…”
Section: Introductionmentioning
confidence: 99%
“…The deviation from the Boltzmann-Gibbs statistics is small at high energies, and the values of |1−q| are close to 0.1. The effects of the small deviation from a e-mail: m isihar@koriyama-kgc.ac.jp the Boltzmann-Gibbs statistics on physical quantities, such as correlation and fluctuation [22,[26][27][28][29], have been studied.…”
Section: Introductionmentioning
confidence: 99%